Qualitative study of homecare and death beliefs among HIV/AIDS and cancer relatives - Barbieri, André Luiz; Machado, Alcyone Artioli; Figueiredo, Marco Antônio de Castro (Paidéia (Ribeirão Preto), 2005)
AIDS and cancer have incited prejudiced attitudes of segregation and fear; however, the constant work of people involved with care taking made respectable and humanitarian life possible to individuals that were taken ill. The present study has the objective of surveying the beliefs of the HIV/AIDS and cancer patients relatives related to death and home care. Therefore separate and semi-structured appointments were done with 15 relatives of HIV sick people and 10 relatives of cancer patients based on procedures of evocation-enunciation-verification to survey the beliefs related to death and home care. The beliefs surveyed demonstrate the lack of preparation and the difficulties that relatives have towards death and care of the patients. It is observed the need of creating projects that would aim emotional advising and aid to patients and relatives as well.